New contributions to the Hamiltonian and Lagrangian contact formalisms for dissipative mechanical systems and their symmetries - Gaset, Jordi; Gràcia, Xavier; Muñoz-Lecanda, Miguel C.; Rivas, Xavier; Román-Roy, Narciso (International journal of geometric methods in modern physics, 2020)
We provide new insights into the contact Hamiltonian and Lagrangian formulations of dissipative mechanical systems. In particular, we state a new form of the contact dynamical equations, and we review two recently presented Lagrangian formalisms, studying their equivalence. We define several kinds of symmetries for contact dynamical systems, as well as the notion of dissipation laws, prove a dissipation theorem and give a way to construct conserved quantities. Some well-known examples of dissipative systems are discussed.